Group membership salience, social dominance orientation and task performance - Botha, Corlia (Organisational Psychology, 2014)
The use of teams in organisations is often plagued by reduced individual effort which is termed social loafing. Therefore the study proposed that by making people aware that they are part of a group and introducing intergroup competition, social loafing would be reduced and turned into social labouring. The study further investigated the potential mediating effect of social dominance orientation on the relationship between group membership salience and task performance.